Marine microbiology :Bioactive compounds and biotechnological applications - Kim, Se-Kwon
Marine microbial biotechnology comes of age. This unique reference describes commercially important compounds produced by marine microorganisms with applications in the pharmaceutical, nutraceutical, food and veterinary fields.--